Korelasi Dampak Aktivitas Perdagangan Internasional Terhadap Kerusakan Lingkungan - Alfan Dzikria Nurrachman; Iramadya Dyah Marjanah (Amal Insani Foundation, 2023)
International trade activities require a rule as an important support to regulate the process of running the elements of international trade so that it is as effective as it should be. Gradually, the international trade system is beginning to understand more deeply the impacts arising from environmental damage. Attention to the issue of climate change and environmental damage in the midst of the international trade system has become an issue that has been highlighted since the growing awareness of environmental sustainability. The focus of this article's discussion is on the issue of the impact of climate change in the midst of international trade. The research method used in conducting this research is to use normative study methods, using secondary data obtained through literature searches. The purpose of this study is to determine the relationship of climate change that occurs as a result of international trade activities. The results of the study show that international trade activities have quite a serious impact on environmental change or climate change. One example is in the production of cereals which can hamper international trade activities. So that the parties in authority can take preventive steps to prevent environmental damage.